Filling Procedures for Lip and Perioral Rejuvenation: A Systematic Review - Pascali, Michele; Quarato, Davide; Carinci, Francesco (Rejuvenation research, 2018)
The ideal perioral and lip rejuvenation technique provides the longest period of efficacy, lowest complication rate, and best esthetic results. Genetics, intrinsic aging, sun exposure, and repetitive muscle twitching of the orbicularis oris produce angular, radial, and vertical lines of the perioral lines and, for this reason, the needs of patients in the treatment of this anatomical area can range from simple lip enhancement to a broader and more comprehensive treatment with simultaneous correction of perioral wrinkles. A myriad of materials have been described for rejuvenation of this area. At present, the most popular and commonly used lip enhancers are dermal fillers, but there is still no agreement on what the best material for filling soft tissue of the face and in particular of the perioral region is. This systematic review will focus on the various dermal fillers, of different materials approved by the US Food and Drug Administration (FDA) namely poly-L-lactic acid, calcium hydroxylapatite, and hyaluronic acid and also different grafts, for perioral rejuvenation, with the goal of determining the optimal approach. A systematic search for English studies involving perioral rejuvenation was performed using these databases: PubMed, Google Scholar, and Ovid, using a combined keyword search or medical subject headings. At the end of our study selection process, 17 relevant publications were included. For each study, year of publication, type of material used for filling, number of patients, subject of study assessment, and efficacy of the filler procedure for lip rejuvenation were analyzed.